Mars Advanced Radar for Subsurface and Ionospheric Sounding (MARSIS) after nine years of operation: A summary. (July 2015) - Orosei, R.; Jordan, R.L.; Morgan, D.D.; Cartacci, M.; Cicchetti, A.; Duru, F.; Gurnett, D.A.; Heggy, E.; Kirchner, D.L.; Noschese, R.; Kofman, W.; Masdea, A.; et al.
Abstract: Mars Express, the first European interplanetary mission, carries the Mars Advanced Radar for Subsurface and Ionosphere Sounding (MARSIS) to search for ice and water in the Martian subsurface. Developed by an Italian–US team, MARSIS transmits low-frequency, wide-band radio pulses penetrating below the surface and reflected by dielectric discontinuities linked to structural or compositional changes. MARSIS is also a topside ionosphere sounder, transmitting a burst of short, narrow-band pulses at different frequencies that are reflected by plasma with varying densities at different altitudes. The radar operates since July 2005, after the successful deployment of its 40 m antenna, acquiring data at altitudes lower than 1200 km. Subsurface sounding (SS) data are processed on board by stacking together a batch of echoes acquired at the same frequency. On ground, SS data are further processed by correlating the received echo with the transmitted waveform and compensating de-focusing caused by the dispersive ionosphere. Ground processing of active ionospheric sounding (AIS) data consists in the reconstruction of the electron density profile as a function of altitude. MARSIS observed the internal structure of Planum Boreum outlining the Basal Unit, an icy deposit lying beneath the North Polar Layered Deposits thought to have formed in an epoch in which climate was markedly different from the current one. The total volume of ice in polar layered deposits could be estimated, and parts of the Southern residual ice cap were revealed to consist of ≈ 10 m of CO2 ice. Radar properties of the Vastitas Borealis Formation point to the presence of large quantities of ice buried beneath the surface. Observations of the ionosphere revealed the complex interplay between plasma, crustal magnetic field and solar wind, contributing to space weather studies at Mars. The presence of three-dimensional plasma structures in the ionosphere was revealed for the first time. MARSIS could successfully operate at Phobos, becoming the first instrument of its kind to observe an asteroid-like body. The main goal pursued by MARSIS, the search for liquid water beneath the surface, remains elusive. However, because of the many factors affecting detection and of the difficulties in identifying water in radar echoes, a definitive conclusion on its presence cannot yet be drawn.